TESTICULAR TUBERCULOSIS: A CASE REPORT - Harahap, Andre Lazuardi; Papriska, Fauriski Febrian; Sigumonrong, Yacobda H (Indonesian Journal of Urology, 2018)
Objective: We report a patient with unilateral testicular tuberculosis, referred to Haji Adam Malik Hospital, Medan, Indonesia. In this report we stressed on the findings in the physical examination of the patient, so it can be applied for the other case of testis tuberculosis. Case Presentation: A 3-years old boy came to the Hospital with a painless unilateral right scrotal enlargement. Based on the data from anamnesis, physical examination and laboratory testing, a diagnosis of right testicular tumor was made and the patient was planned for a right radical orchidectomy. Discussion: He was underwent of right orchidectomy and the histological findings and diagnosis was specific tuberculosis. No specific symptom of tuberculosis was found. On the physical examination, general state was normal. The local state was difficult to differentiate with testicular tumor. In the absence of a histology finding, the diagnosis of TB testis may be impossible (Shugaba et al., 2012). Patients with testicular masses should be fully investigated preoperative and post-operative in order to increase the diagnostic index of this condition. However, unilateral or bilateral Testicular Tuberculosis is uncommon and the report said that there are two patients with unilateral testicular tuberculosis referred to Sina Hospital Tehran University of Medical Science (Hassan et al., 2009). Conclusion: TB infection diagnosis might be missed when clinical findings assume a tumor (Hamm, 1997). Physical examination findings may include a non-tender or tender sensible nodule, dilation and thickening of the epididymis (Hassan et al., 2009). Testicular involvement may be either unilateral or bilateral. The clinical history of patients such as contact with lung tuberculosis patient and immune deficiency condition are not always helpful in diagnosis. Although it is a very rare disease, the clinician should consider tuberculosis of the testis as a possible differential of a scrotal mass especially in endemic area like Indonesia (Mbala et al., 1997). This will increase the possibility of early diagnosis, as well as proper and early management. And also have to remember that not testicular tuberculosis itself should be suspected, others kind of disease mimicking symptoms like hydrocele, spermatocele, epididymo-orchitis, non-hodgkin lymphoma, spleenogonadal fusion, and an adrenal rest or a second testis need to be considered.